1997
DOI: 10.1021/ic970513f
|View full text |Cite
|
Sign up to set email alerts
|

Low-Spin Iron(III) Chiroporphyrins:  1H NMR Studies of Cyanide and Substituted Imidazole Coordination

Abstract: Low-spin complexes of iron(III) chiroporphyrin, obtained from (1R)-cis-caronaldehyde acid methyl ester and pyrrole as the atropisomer, with R-imidazoles and cyanide have been studied by means of 1D and 2D (1)H NMR spectroscopy. A complete spectral assignment of resonances has been done on the basis of observed scalar, NOE, and EXSY correlations in 2D COSY and NOESY experiments. The chemical shift of beta-H pyrrole resonances have been used as a sensitive probe of electronic state of iron(III) metal ion. Cyanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 49 publications
6
77
0
2
Order By: Relevance
“…[7,[81][82][83] This unique spectroscopic feature can be related to the extensive ruffling of the macrocycle, [82,[84][85][86] equatorial C-coordination, and/or axial pyridine coordination. [7] A conformational rearrangement process was detected which involves two structures differentiated by macrocyclic ruffling.…”
Section: Low-spin Organoiron(iii) N-confused Pyriporphyrinmentioning
confidence: 99%
“…[7,[81][82][83] This unique spectroscopic feature can be related to the extensive ruffling of the macrocycle, [82,[84][85][86] equatorial C-coordination, and/or axial pyridine coordination. [7] A conformational rearrangement process was detected which involves two structures differentiated by macrocyclic ruffling.…”
Section: Low-spin Organoiron(iii) N-confused Pyriporphyrinmentioning
confidence: 99%
“…Recentemente, uma vasta literatura vem sendo publicada abordando as conformações do anel porfirínico, as relações com a configuração de spin eletrônico do centro férrico, suas implicações físico-químicas como reatividade e potencial redox e repercussões espectroscópicas nas várias técnicas empregadas. 137,146,[154][155][156][157][158] Dentre estas técnicas, vale mencionar o emprego amplamente difundido da ressonância magnética nuclear (RMN), fazendo uso, no caso do centro férrico (Fe(III)), do acoplamento hiperfino para sondar a conformação e as circunvizinhanças do anel porfirínico. O emprego desta técnica espectroscópica para avaliar a interação hiperfina abrange os núcleos dos ligantes axiais, os núcleos do anel porfirínico e também a interação com o spin nuclear dos núcleos pertencentes aos resíduos de aminoácidos formadores dos limites da cavidade do bolsão hidrofóbico do heme.…”
Section: A Configuração Eletrônica Dos Grupos Heme Férricos Para Os Sunclassified
“…The former studies generally indicated that the electronic ground state was (d xy ) 2 (d xz ,d yz ) 3 for these complexes. However, more recently, it was shown that the bis(cyanido) complexes of meso-substituted Fe III porphyrins having alkyl substituents of increasing size [17] and other iron(III) porphyrins having bulky substituents in the meso position [18][19][20][21] show a large shift in the pyrrole protons towards the diamagnetic region, which is indicative of a large contribution of the unusual (d xz d yz ) 4 2 ] appear at very high magnetic field (δ = -10 to -20 ppm). This large upfield shift of the β-pyrrole protons indicates the existence of large spin densities on the β-pyrrole carbons, which is induced by the interactions between porphyrin 3e g and iron d π orbitals.…”
Section: Electronic Ground State Of Low-spin Complexesmentioning
confidence: 99%